488 Sharps injuries among health care personnel in a chinese hospital. (24th April 2018) - Xiaoxia, L; Adam, B
Abstract : Introduction: Sharps injury is a penetrating wound from a needle, scalpel, or another sharp object that may result in exposure to blood or other body fluids. Sharps injuries constitute a serious occupational health problem for health care personnel and can result in high direct and indirect costs for the health care facility. The aim of the study was to examine the prevalence and characteristics of sharps injuries among Chinese health care workers. Methods: A questionnaire survey was carried out in a Chinese hospital to collect demographic and occupational data, information on sharps injuries and their reporting. Multiple logistic regression was used to analyse the potential risk factors of sharps injuries, including gender, age, education level, position, department and perception of the safety culture. Results: The 5 year prevalence of sharps injuries was found 41% among the hospital personnel. Sex, age and education did not influence significantly sharps injuries (p=0.798, p=0.886 and p=0.47, respectively). However, the position of staff and especially the department where they work significantly correlated with sustaining such an accident (p=0.025 and p<0.0001, respectively). 86% of accidents hurt fingers, 90% of injuries were sustained in inpatient units. Six sharp devices were responsible for nearly 95% of all injuries and 86% of them occurred when health care workers were using the devices. Association could not be described between sharps injuries and the perceived culture of safety. About three-fourth of sharps injuries were not reported. Discussion: A high prevalence rate of sharps injuries was observed in the studied hospital, the majority of injured workers were nurses. The rate varied significantly by department and position. The study found significant under-reporting. Adequate level of occupational health and safety for health care personnel can only be provided with efficient prevention from sharps injuries, which needs information on risk factors and a well-functioning reporting system.